The Role of Women in Increasing Oil Palm Production in Aceh Province - Mawardati Mawardati; Rozanna Dewi; Khalsiah Khalsiah; Yesy Afriliia; Gilang Ramadhan; Andra Munandar (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
Regional development is largely determined by the potential possessed by a region, the wisdom made by the local government must refer to the potential of areas that have the opportunity to be developed, especially the plantation subsector. The high demand for exports of plantation products has encouraged the development of a number of plantation commodities in various regions. Palm oil is one of the leading commodities in the plantation subsector in Aceh Province. Until now, oil palm is a prima donna crop of the people in the Aceh region and in several other regions. Palm oil is the development of an agribusiness-based plantation subsector. The activities of oil palm plantations and their derivative products provide high added value in the economic sector. The importance of developing oil palm plantations is increasingly felt in the impact on the workforce of both men and women who work in the oil palm plantation sector and its derivative sectors. Women are an important part of the palm oil industry that is always present in every chain of the palm oil production process. This impact can be seen from the increase in income of the farming community, resulting in an increase in the purchasing power of rural people, both for primary and secondary needs. Based on the role of oil palm in the rural economy and the development of oil palm plantation areas in the Aceh area. The selection of research sites is in the Western region of Aceh which includes: Aceh Singkil and Meulaboh Regencies and the Eastern region of Aceh includes: North Aceh Regency, East Aceh, Kuala Simpang. It is known that the region has many characteristics of the oil palm plantation industry in Aceh province.